Perros y Humanos: una conjunta construcción emocional de la cotidianeidad - Pedro Tomé (Nuevo mundo - Mundos Nuevos, 2021)
Starting from on an ethnographic research, the article raises the need to establish a new theoretical framework to understand how are relationships constructed by the coexistence between humans and dogs. Although market conditions sometimes make dogs a commodity, an object of consumption, and a class marker, affective ties go beyond these conditions with effects on various levels that transcend the individual and spread throughout the city through interspecies groups who walk together through the streets and parks.